Trouble felt in Education and Sustainability during the Time of Covid-19 in Nepal: Responses of Teachers, Parents and Students - Dahal, Tika Ram (Medha: A Multidisciplinary Journal, 2023)
Examined in this study are crisis-related educational initiatives. Its goal is to analyse the educational approaches employed in Nepal's community schools during the COVID-19 pandemic-caused catastrophe. This study is qualitative, hence the methodology employed is deemed appropriate. In this study, the data are collected through purposeful sampling. The participants are dedicated teachers from particular schools, as well as kids and parents. The study was conducted in the Kageshwori Manohara Municipality in the Kathmandu district. The study's primary sources are the participants, hence primary sources were used to collect the data. Using narrative enquiry and qualitative approaches, the data are analysed. Interviews were used to collect the data because it was a qualitative study. Narrative enquiry is used in the study, which follows the interpretative paradigm. Inductive and qualitative research approaches are thus both used in this study. The difficulties and crises that teachers, students, and parents experienced in Nepal during COVID-19 are examined in this paper. According to reports, COVID-19 has caused unforeseen changes in people's lifestyles. It prompted the development of online education, which promoted the use of modern technology although financial crisis disturbed sustainability of people. The results of this study demonstrate the technical and economical difficulties of adopting online classes in COVID-19. It is expected that this study will have an impact on society and academia. This study has preserved the value of originality because it is based on primary sources.